(untitled) (Journal of Namibian Studies : History Politics Culture, 2022)
To receive reparations from Germany for the first genocide of the 20th century, the Herero of Namibia have been facing a legal challenge; they must demonstrate that the Herero genocide was illegal under international law during the colonial period. Through the analysis of historical treaties and documents, this article reveals that the Herero can make use of legal evidence to support their demands. The article demonstrates that Germany violated contemporaneous international law, i.e. the international law valid at the time. This revelation has significant implications for Namibia as well as for other victims of colonial genocides. The article then comments on the political context and suggests possible routes for the Herero to secure reparations for the tragedy their ancestors experienced.